Assessing the Level of Reading Comprehension and Reading Strategies Among Criminology Students - Dunggo-an , Jay O.; Gulam , Annielaine S.; Pantilgan, Ryan Chris J.; Catubig, Daisy (Journal of Education and Learning Reviews, 2025)
Background and Aim: Reading comprehension is essential as it significantly impacts a student’s life and serves as the foundation for learning. In Criminology, strong reading skills enable students to understand legal frameworks, engage with theoretical concepts, evaluate research, analyze policies, communicate effectively, and think critically about complex issues related to crime and justice. This study examines the levels of reading comprehension and the reading strategies used by Criminology students at a private college in Pagadian City during the 2024-2025 academic year. Materials and Methods: This study employs a descriptive quantitative research design involving 113 Criminology students from a higher education institution in Pagadian City during the 2024-2025 academic year. The first tool used is the Reading Comprehension Test developed by Yan (2011), consisting of 20 multiple-choice questions based on four passages. The second tool is the Reading Strategies Checklist, also created by Yan (2011), which helps participants in reading and answering questions, ranging from 1 to 30 items. Results: The researchers used the Pearson correlation coefficient to evaluate the relationship between reading strategies and reading comprehension among BS Criminology students. The results indicated that participants had poor reading comprehension, with an average score of 35.58%. In contrast, their reading strategies score was 1.77, categorized as "Good." Despite this, the analysis revealed no significant relationship between reading strategies and comprehension, as evidenced by a p-value of 0.903, which exceeds the conventional significance threshold of 0.05. Consequently, it can be concluded that reading strategies do not significantly impact reading comprehension in this group of students. Conclusion: Remedial and enrichment activities in English language literacy and incredibly dedicated reading time on Fridays are crucial for enhancing students’ comprehension and preparing them for law enforcement careers. Teachers can support this by providing relevant reading materials and assigning reporting tasks. Future research should focus on qualitative studies that explore the experiences of Bachelor of Science in Criminology students. In-depth interviews can reveal the connections between their academic journeys and personal development, offering valuable insights into their lived experiences in the field.